Peran Dana Perimbangan Terhadap Kemiskinan di Provinsi Bali - Arie Ismail; Abdul Hakim (Jurnal Aplikasi Bisnis, 2017)
This study analyzed the impact of balanced funds that consist of the Revenue Sharing (DBH), General Allocation Fund (DAU), and the Special Allocation Fund (DAK), population, level of education and health to the amount of poverty in the province of Bali. This study is a panel data analysis consists of nine districts or cities in 2006-2011. The results showed that DBH, DAU, education, and health have negative effects to the amount of poverty and population has no correlation with the poverty.